Space Window : Man in space and space in art. - Brown University, Providence; Breton, André; Bunnell, Sterling; Calder, Nigel; Clarke, Arthur C.; Collins, Michael; Eisley, Loren; Hale, George Ellery; Jahn, Ernest; Jung, Carl Gustav; Kybalion, The; Michell, John; et al. (Providence : Brown University, 1977)
Abraham, Raimund ; Ant Farm ; Borofsky, Jonathan ; Broders, Addison ; Byrne, Francis ; Carpenter, Jamie ; Carson, Neke ; Chao, Bruce ; Chase, Louisa ; Chihuly, Dale ; Cifrino, Peter ; Coburn, John ; Congdon, Dennis ; Curry, Susan ; Dalglish, James ; Drew, William ; Fishman, Richard ; Florian, Friedrich St. ; Fraser, pam ; Gallery, Bill ; Garber, Richard Fleischner & Ira ; Gaylord, William ; Gosh, Dan ; Gunderson, Karen ; Guy, Michael ; Harned, Richard ; Harris, Suzanne ; Helander, Bruce ; Hendricks, Roger ; Heuser, Tayo ; Highstein, Gene ; Hines, Kathy ; Horniak, Gregor ; Jensen, Bill ; Johansen, Christen ; JohnTorreano ; Kaneko, Jun ; Keck, Hardu ; Komoski, Bill ; Koons, Jeff ; Kovacs, Andrea ; Krot, Paul ; Lenkowsky, Marilyn ; Leslie, Seaver ; Lieberman, Louis ; Loeffler, A.J. ; Marcus, David ; Marin, John ; Mayer, Roger ; merkin, Richard ; Moscowitz, Robert ; Mueller, Louis ; Murray, Elizabeth ; Ockerse, Tom ; Oneal, Robert ; Oppenheim, Dennis ; Pfaff, Judy ; Pierucci, Massimo ; Richardson, Dean ; Rockhill, Morgon ; Ross, Charles ; Rossi, Greg ; Rothenfeld, Daniel ; Saret, Alan ; Savage, Michael ; Scanga, Italo ; Slater, David ; Slavonic, John ; Smith, Nancy ; Speiser, Kenn ; Sprayregen, Jill ; Statom, Therman ; Torlen, Michael ; Trouvelot, E.L. ; Vaterlaus, Eve ; Waltemath, Joan ; Warren, Kit ; Witz, Robert ; Wulff, Viki
Space Window : Man in space and space in art, Brown University, Providence, September 14 - October 6, 1977
Engels
boek